An assessment on glare from daylight through various design of shading devices in hot humid climate, case study in Kuala Lumpur, Malaysia - Denan, Zuraini; Abdul Majid, Noor Hanita (2014)
Glare is one of the main problems that cause daylight to be visually undesirable in a hot humid country such as Malaysia. However, the design of modern buildings in Malaysia applies large glass windows and some partially covered with various design of shading devices, which are merely for aesthetic reason. Having sun shading devices have not solved the glare problems instead create either dark interiors or force for interior blinds and use of electrical lighting. Thus, this paper aims to investigate the glare performance under daylight through most common types of shading devices used in Kuala Lumpur, Malaysia. The four most common shading devices are: vertical, horizontal, egg-crate and geometrical pattern. The experiment covers the luminance, illuminance level and subjective responses of the occupants. The result indicates that under the vertical shading devices has spotted the highest glare values, in contrast subjective response indicate that the vertical shading devices provide most comfortable environment.